A Combination of Vitamin C and Losartan for Cisplatin-induced Nephrotoxicity in Rats (Iranian Journal of Kidney Diseases, 2012)
Introduction. The nephroprotective effect of co-administration of vitamin C and losartan as prophylaxis against cisplatin-induced nephrotoxicity (CIN) was evaluated. Materials and Methods. Co-administration of vitamin C and losartan was compared with losartan (10 mg/kg), vitamin C (250 mg/kg), and placebo in 4 groups of rats with CIN. The prophylactic agents were injected daily for a period of 4 days, and on day 3, a single dose (6 mg/kg) of cisplatin was administrated. The animals were sacrificed 7 days later for pathological examination of the kidneys. Results. Cisplatin prevented the animals' weight gain. The serum levels of creatinine and blood urea nitrogen increased within the groups with CIN, but no significant difference was observed between the groups. The prophylaxis has no effect on serum osmolality, total protein, or nitrite concentrations. The kidney tissue damage was scored, and losartan provided a lower damage score than vitamin C and a combination of vitamin C and losartan. Conclusions. We concluded that co-administration of vitamin C and losartan was not more effective than the administration of vitamin C or losartan alone.